Harm reduction in name, but not substance: a comparative analysis of current Canadian provincial and territorial policy frameworks - Elaine Hyshka (Harm Reduction Journal, 2017)
Abstract Background In Canada, funding, administration, and delivery of health services—including those targeting people who use drugs—are primarily the responsibility of the provinces and territories. Access to harm reduction services varies across jurisdictions, possibly reflecting differences in provincial and territorial policy commitments. We examined the quality of current provincial and territorial harm reduction policies in Canada, relative to how well official documents reflect internationally recognized principles and attributes of a harm reduction approach. Methods We employed an iterative search and screening process to generate a corpus of 54 provincial and territorial harm reduction policy documents that were current to the end of 2015. Documents were content-analyzed using a deductive coding framework comprised of 17 indicators that assessed the quality of policies relative to how well they described key population and program aspects of a harm reduction approach. Results Only two jurisdictions had current provincial-level, stand-alone harm reduction policies; all other documents were focused on either substance use, addiction and/or mental health, or sexually transmitted and/or blood-borne infections. Policies rarely named specific harm reduction interventions and more frequently referred to generic harm reduction programs or services. Only one document met all 17 indicators. Very few documents acknowledged that stigma and discrimination are issues faced by people who use drugs, that not all substance use is problematic, or that people who use drugs are legitimate participants in policymaking. A minority of documents recognized that abstaining from substance use is not required to receive services. Just over a quarter addressed the risk of drug overdose, and even fewer acknowledged the need to apply harm reduction approaches to an array of drugs and modes of use. Conclusions Current provincial and territorial policies offer few robust characterizations of harm reduction or go beyond rhetorical or generic support for the approach. By endorsing harm reduction in name, but not in substance, provincial and territorial policies may communicate to diverse stakeholders a general lack of support for key aspects of the approach, potentially challenging efforts to expand harm reduction services.